Impact of different nitrogen sources on the growth of Arthrospira sp. PCC 8005 under batch and continuous cultivation – A biochemical, transcriptomic and proteomic profile. (August 2017) - Deschoenmaeker, Frédéric; Bayon-Vicente, Guillaume; Sachdeva, Neha; Depraetere, Orily; Cabrera Pino, Juan Carlos; Leroy, Baptiste; Muylaert, Koenraad; Wattiez, Ruddy
Highlights: Impact of transition in different N sources on Arthrospira sp. was evaluated. First investigation using multiple omic approaches on batch and continuous cultures. Urea was observed be a better nitrogen source compared to nitrate and ammonium. NH4 + showed modifications in proteome and EPS profiles indicating a cellular stress. NH4 + showed a repressive effect on nitrate-assimilation pathway. Abstract: The aim of the present study was to evaluate the effects of varying concentrations of different nitrogen sources (individually or in combination) on the biochemical, transcriptomic and proteomic profiles of Arthrospira sp. PCC 8005 under batch and continuous modes. In batch mode, while ammonium showed a repressive effect on nitrate-assimilation pathway of the cyanobacteria; better growth and nutrient uptake rate were observed in presence of urea than nitrate. The inhibitory effect of ammonium was further confirmed by the continuous photobioreactor study wherein the nutrient feed was transiently replaced from nitrate to ammonium (28 mM turbiostat regime). The changes in lipid, exopolysaccharide, transcriptomic and proteomic profiles of cyanobacteria on transition from nitrate to ammonium indicated at an onset of nutrient stress.